Tafseer of the Quranic Verses on Social Justice: Historical and Contemporary Perspectives - Mr. Abdullah; Mr. Abdul Samad (Journal of Religion and Society, 2025)
The Quranic teachings on social justice form a cornerstone of Islamic ethics, emphasizing fairness, equity, and the welfare of marginalized communities. This study examines the historical and contemporary tafseer (exegesis) of Quranic verses related to social justice, comparing classical and modern interpretations to highlight their evolving application. Classical scholars such as Al-Tabari, Ibn Kathir, and Al-Qurtubi grounded their analyses in linguistic precision and historical context (asbab al-nuzul), addressing issues like wealth redistribution (zakat), judicial equity, and anti-tribalism within medieval societal frameworks. Their works laid the foundation for Islamic social justice, though their interpretations occasionally reflected patriarchal and hierarchical norms of their time. In contrast, contemporary scholars like Fazlur Rahman, Amina Wadud, and Khaled Abou El Fadl employ interdisciplinary approaches, integrating sociology, feminism, and critical theory to address modern challenges such as systemic racism, gender inequality, and economic exploitation. Modern tafseer prioritizes the Quran’s ethical objectives (maqasid al-shari'ah), advocating for transformative justice in areas like Islamic finance, human rights, and environmental ethics. Movements such as Islamic feminism (e.g., Musawah) and liberation theology (e.g., Farid Esack’s work) exemplify this progressive reinterpretation, challenging traditional patriarchal and elitist readings. The study underscores the dynamic interplay between tradition and innovation, demonstrating how Quranic principles remain relevant across epochs. While classical exegesis provides theological rigor, contemporary tafseer ensures adaptability to 21st-century issues, fostering a holistic vision of justice that bridges scripture and activism. Keywords: Social Justice, Quranic Exegesis (Tafseer), Classical Scholarship, Contemporary Interpretations, Maqasid Al-Shari'ah, Islamic Feminism, Economic Equity, Systemic Oppression, Zakat, Hermeneutics